PENGARUH JUMLAH SIMPANAN TERHADAP PEROLEHAN SISA HASIL USAHA PADA KOPERASI DHARMAGHATI KSATRIA JAYA CIMAHI PERIODE 2011 – 2015 - Herlys Prasasti; Hadi Juwanda (Journal of Business Administration, 2022)
The purpose of this study was to determine the influence of the total deposits to the acquisition of net income at Cimahi Dharmaghati Ksatria Jaya Coorperative, periods of 2011-2015. The method used quantitative and descriptive methods. Analysis of the data used Kolmogorov-Smirnov normality data test, Pearson Product Moment Correlation Analysis, Linear Regression Analysis, determination coefficient and hypothesis test (t test). The results of the data normality test was 0.853 above 0.05, which that both variables were normally distributed. Then the results of the Pearson product moment correlation analysis was 0.830, which meant the amount of deposits with the acquisition of net income had a very strong correlation. Moreover, the results of the coefficient of determination was 68.9%. It showed that net income was influenced by the amount of deposits amounted to 68.9%. Yield data from linear regression analysis was Y = 197.125 + 0.14 X. Moreover, the results of the hypothesis test (t test) was t-count < t-table (2.574 <3.182), the amount of deposits did not significantly influence net income. The problems that occurred at Cimahi Dharmaghati Ksatria Jaya Coorperative the number of deposits and the acquisition of net income from the coorperative members who took his mistress but still had the right to apply for loans. Furthermore, the decrease in loan interest rates occured. The writer suggest based on the above problems where members who already do not have the savings are not entitled to make loans and coorperative provides loan rates based on the term of loan